L’Université américaine dans le débat public après le 11 septembre - Pierre Guerlain (Revue LISA)
The various reactions to 9/11 in the academic community and the attacks on U.S scholars and campuses are analyzed in this article. One particular text is chosen for close scrutiny: ACTA’s “Defending Civilization: How Our Universities Are Failing America And What Can Be Done About It” The view taken here is that the atrocities of 9/11 have been instrumentalized in order to further discredit the humanities and social science departments of American universities that have been under attack at least since the so-called “culture wars”. The so-called war on terrorism threatens the civil liberties that some academics wish to preserve.